Հայոց ցեղասպանության տարիներին հայերի իրական և կեղծ փրկության խնդրի շուրջ - Հ. Տ. Մարության (ՀՀ ԳԱԱ հրատ.)
В последнее время, на фоне попыток урегулирования армяно-турецких отношений, большое внимание уделяется вопросу спасения армян со стороны турок в годы геноцида. В свете научного рассмотрения проблемы необходимо уточнить понятие “спасение”. Recently a great attention is devoted to the issues of rescue of Armenians by Turks during the Armenian Genocide on the background of attempts of regulation of Armenian-Turkish relations.When discussing the problem in the scholarly dimension, the necessity of clarification of the term “rescue” is emerged.
Keywords: History; Armenian Genocide (1915); D History